Predyktory wrażliwości moralnej pielęgniarek i położnych w praktyce klinicznej – badanie przekrojowe - Dziurka, Magdalena; Jedynak, Anna; Jurek, Krzysztof; Dobrowolska, Beata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
Moral sensitivity, which encompasses the ability to identify and respond to ethical issues in care, is essential for healthcare professionals to effectively manage complex clinical scenarios and suport patient autonomy. The aim of this study was to assess the moral sensitivity of nurses and midwives and its predictors and to assess the psychometric properties of the Polish version of the Moral Sensitivity Questionnaire Revised (MSQ-R-Pol). A cross-sectional study was conducted among 683 midwives and nurses working in hospitals in Poland. The 2-component 9-item MSQ-R-Pol is a reliable tool with satisfactory psychometric properties. The predictors of moral sensitivity were: higher age, having children, very good material conditions, working with adult patients aged 18 to 65 years and neonatal/infant patients. The findings also reveal a negative correlation between moral sensitivity and various workplace issues, such as team relationships and professional competence limitations. There was no difference in moral sensitivity between nurses and midwives, nor in the sensitivity of this group measured before and during COVID-19 pandemic. The MSQ-R-Pol is a reliable and valid tool adapted to cultural conditions. Hospital managers and policymakers should focus their future actions on predictors of moral sensitivity, such as organisational issues, the specific characteristics of work in a particular ward and patient populations, by supporting nurses and midwives in ethical decision-making, the development of their ethical competencies, positive leadership and the development of resilience.